Green Choices: The Role of Green Skepticism and Eudaimonic Well-Being in Evoking Green Purchase Intention - Mitariani, Ni Wayan Eka; Agus Wahyudi Salasa Gama; Nilna Muna (Universitas Pendidikan Ganesha, 2025)
Nowadays, companies are competing to produce green products to maintain sustainability. However, consumer responses to these efforts are still varied. This research aimed to investigate the impact of green skepticism on the relationship between expected eudaimonic well-being and green purchase intention. Additionally, the mediating role of expected eudaimonic well-being in the relationship between green brand awareness, green brand image, and green purchase intention. The approach of this research is quantitative research. Data collected from 250 respondents using questionnaire and were analyzed using SEM-PLS. Respondents of this research were people in Bali, who had knowledge about green products. The result found expected eudaimonic well-being significantly affect the green purchase intention. Green brand awareness and green brand image have no direct effect to green purchase intention. Green brand awareness and green brand image indirectly affect the green purchase intention through expected eudaimonic well-being. The interaction of expected eudaimonic well-being and green skepticism has no significant effect on green purchase intention. The findings in the paper provide clear evidence supporting the Behavioral Reasoning Theory. The results of this study also confirm that eco-friendly products are a brand's commitment to sustainability, requiring brands to consider long-term impacts, provide benefits to communities, and increase consumer awareness of the products they offer. To overcome consumer skepticism, brands need to visibly commit to sustainability, educate customers, and transparently communicate their values and commitment to the environment.